2020
DOI: 10.1074/jbc.ra120.014104
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-transporting ABC transporters are defined by a conserved D/E-P motif regulated by a prolylisomerase

Abstract: The plant hormone auxin must be transported throughout plants in a cell-to-cell manner to affect its various physiological functions. ABCB transporters are critical for this polar auxin distribution, but the regulatory mechanisms controlling their function is not fully understood. The auxin transport activity of ABCB1 was suggested to be regulated by a physical interaction with FKBP42/Twisted Dwarf1 (TWD1), a peptidylprolyl cis-transisomerase (PPIase), but all attempts to demonstrate such a PPIase activity by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…In light of the clinical importance of CFTR, it is surprising that interacting surfaces and respective prolines have not yet been mapped and/or identified. While for FKBP42/ TWD1-ABCB1 interaction it was shown that the FKBD interferes with the NBD2 containing P1008 [58], FKBP38-CFTR contacts and PPIase-relevant prolines have not yet been determined. Moreover, despite the fact that AtABCB1 P1008 seems to be conserved in the loop between TMD2 and NBD2 of CFTR [58], it will be interesting to see if the three prolines in the R domain of CFTR [86] are directly altering CFTR activity or the affinities for regulatory kinases, or both.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In light of the clinical importance of CFTR, it is surprising that interacting surfaces and respective prolines have not yet been mapped and/or identified. While for FKBP42/ TWD1-ABCB1 interaction it was shown that the FKBD interferes with the NBD2 containing P1008 [58], FKBP38-CFTR contacts and PPIase-relevant prolines have not yet been determined. Moreover, despite the fact that AtABCB1 P1008 seems to be conserved in the loop between TMD2 and NBD2 of CFTR [58], it will be interesting to see if the three prolines in the R domain of CFTR [86] are directly altering CFTR activity or the affinities for regulatory kinases, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, CFTR opening by cyclophilin A is reversed by cyclosporin A known to inhibit its PPIase activity, providing strong evidence that ABC transport activation can depend on peptidylprolyl isomerization. This concept was recently hardened by demonstrating that transport activation of Arabidopsis ABCB1 by FKBP42/TWD1 was absent, when P1008 located at the surface of NBD2 was mutated to alanine [58]. As said before, direct evidence for any ABC transporter as a substrate for FKBP PPIase is missing and methods to identify PPIase ‘hot’ prolines are not available.…”
Section: X‐proline Residues As Possible Molecular Switches Of Abc Tramentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, ABCB transporters play a very important role in the distribution of auxin inside the plant. The activity of ABCB1 transporter was reported to be regulated by peptidyl prolyl cis ‐ trans isomerase (PPIase; Hao et al, 2020). Further characterization of ABCB1 showed the presence of several proline residues in the domain and linker regions.…”
Section: Role Of Abc Transporters In Hormonal Homeostasismentioning
confidence: 99%